Metode Ijtihad Wahbah Zuhaili dan Aktualisasinya Dalam Konteks Kekinian - Akhmad Rizal Amiruddin (STAI Al-Washliyah Banda Aceh, 2021)
Ijtihad is a process of legal reasoning to derive Islamic legal law conducted by qualified and trained jurist. The need for ijtihad dates back to the beginning of Islam, especially after the death of Prophet Muhammad SAW. In Islamic jurisprudence, Ijtihad occupies a special place, which can only be practiced by those qualified to do. As a prominent Islamic Scholar, Wahbah Zuhaili offers new methods for conducting ijtihad. This Article relied on some qualitative approaches to provide answers. That means the results of study were not obtained through some statistical calculations or other quantitative means. This was allowed to understand more detailed or more complex into some phenomena being investigated. For this purpose, library research and content analysis were used as methods for data collection and data analysis respectively. The study revealed that Wahbah Zuhaili relied on specific methods in conducting Ijtihad, which differed quite substantially from those used by many other scholars. It was also revealed that the method used found to be quite relevant to the current era/context.